AGAPP: efficacy of first-line cisplatin, 5-fluorouracil with afatinib in inoperable gastric and gastroesophageal junction carcinomas. A Hellenic Cooperative Oncology Group study. (3rd June 2021) - Zarkavelis, George; Samantas, Epaminontas; Koliou, Georgia-Angeliki; Papadopoulou, Kyriaki; Mauri, Davide; Aravantinos, Gerasimos; Batistatou, Anna; Pazarli, Elissavet; Tryfonopoulos, Dimitrios; Tsipoura, Anna; Bobos, Mattheos; Psyrri, Amanda; et al.
Abstract: Purpose: Gastric cancer is the fifth most common neoplasm worldwide with high rates of mortality. Afatinib, a low molecular, irreversible potent inhibitor of ErbB trans-membrane receptor family, has shown promising results according to preclinical and phase I clinical trial data when combined with chemotherapy. We aimed at evaluating the safety and efficacy of the combination of cisplatin, 5FU with afatinib in molecularly unselected patients with advanced gastric cancer. Methods: Patients with locally advanced or metastatic gastric/gastroesophageal junction adenocarcinoma received first line combination therapy of cisplatin, 5FU and afatinib every 21 days, followed by afatinib maintenance monotherapy. The primary endpoint was the Objective Response Rate (ORR); secondary endpoints included Overall Survival (OS), Progression Free Survival (PFS) and the safety profile. Unplanned exploratory analysis of HER2 and tumor mutational profile was performed. Results: Among 55 patients (ITT population) enrolled, 19 (34.5%) achieved an objective tumor response; stable disease was observed in 16 patients (29.1%) and progressive disease in 10 patients (18.2%). The ORR in the per protocol population (PP) was 42.9%. Within a median follow-up of 56 months, the median PFS and OS in the ITT population was 5.0 and 8.7 months, respectively. Seven of the 47 HER2 informative cases carried HER2 positive tumors while TP53, BRCA2 and SMAD4 were the most frequently mutated genes. The most common toxicities were neutrophil count and white blood cell decrease occurring in 56.4% of patients, followed by anemia (50.9%), hyperglycemia (40%), and diarrhea (38.2%). Conclusions: The combination of cisplatin/5FU with afatinib did not surpass the benchmarks of efficacy of the contemporary therapeutic regimens that are being applied for the treatment of patients with advanced gastric cancer. However, the observed efficacy and the improved safety profile support that our administration schedule may be further investigated to overcome toxicity problems when integrating afatinib to cytotoxic chemotherapy. Clinical trial registration: NCT01743365